Strategi Pemasaran Syariah pada Produk Camilan MPASI Stik Lembut Biji Bunga Matahari - Arsetya, Rafly; Ridlwan, Ahmad Ajib (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine the analysis of sharia marketing strategies for sunflower seed MPASI snacks using marketing mix research instruments with the help of interview data from the 7P aspects, including (Product, Price, Place, Promotion, People, Process, and Physical Evidence). The research methodology used is descriptive qualitative, using primary data sources in the form of interviews with 3 informants, producers, nutritionists and postpartum mothers in the city of Surabaya. The presentation and analysis of the data was carried out based on the source triangulation technique from the results of the interview data. In the marketing strategy analysis using the 7P principles on the basis of fulfilling the behavior of Rasulullah SAW through the 4 mandatory characteristics, namely siddiq, amanah, fatanah, and tablig in the Sunflowsticks sunflower seed MPASI snack product. Thus, resulting in a link between the 4 mandatory characteristics of Rasulullah SAW with the 7P marketing strategy, that Sunflowsticks products are marketable according to the characteristics of shiddiq, able to realize marketing that meets the needs of employees and consumers in the nature of trust, able to create innovation, ideas and novelty from the products being marketed from the nature of fatanah, and being able to provide transparency over the entire business being carried out, capable of meeting the health, halal and safety needs of all babies and children of post-natal mothers